The Effect of Plyometric Training Method and Leg Flexibility toward Side Kick Speed on Male Fighter of Terlat Sakti Club Bengkulu (Journal of Physical Education and Sports, 2019)
This research was motivated by lack of explosive power on male fighters of Pencak Silat Terlat Sakti Club Bengkulu, which resulted in the lack of maximum speed in doing a side kick. The purpose of this study was to find out and analyze: the differences in the influence of single-leg hurdle hop and single-leg bounding plyometric exercises towards the speed of side kick, the differences in the influence between fighters who have high and low leg flexibility towards the speed of side kick, and the interactions between plyometric exercises and leg flexibility towards the speed of side kick. This study uses an experimental design with a 2x2 factorial design. The data analysis technique uses Analysis of Variants (Anova) with a significance level (Î±) of 0.05. The independent variables of this study are the plyometric exercise. High and low leg flexibility considered as attribute variables and the dependent variable is the speed of side kick. The results of this study reveal that: there is a difference in the speed of the side kick on the fighter given in single-leg hurdle hop training with the fighter given in single leg bounding training, there is a difference in side kick speed on fighters who have high leg flexibility with fighters who have low leg flexibility. Thus, it can be concluded that plyometric exercises, as well as leg flexibility, significantly influence the side kick speed on male fighters of Pencak Silat Terlat Sakti Club Bengkulu.